a)
m"\\frac {dv}{dt}" = mg - kv where k>0 is a constant
"m\\frac {dv}{dt}" = - ( kv - mg)
"\\frac {dv}{dt}" = - "\\frac {k}{m}" (v - "\\frac {mg}{k}" )
=> "\\frac {dv}{v - \\frac{mg}{k}}" = - "\\frac {k}{m}" dt
Integrating
"\\int" "\\frac {dv}{v - \\frac{mg}{k}}" = -"\\frac {k}{m}" "\\int" dt
=> ln(v-"\\frac {mg}{k}" ) = -"\\frac {k}{m}" t + C, C is integration constant
By initial condition, when t = 0, v = v0
So C = ln(v0 - "\\frac {mg}{k}" )
Therefore
ln(v - "\\frac {mg}{k}" ) = - "\\frac {k}{m}" t + ln(v0 - "\\frac {mg}{k}" )
=> ln "(\\frac { v - \\frac {mg}{k}}{v_0 - \\frac {mg}{k}})" = - "\\frac {k}{m}" t
=> "(\\frac { v - \\frac {mg}{k}}{v_0 - \\frac {mg}{k}})" = "e^{-\\frac{k}{m}t}"
=> "v - \\frac {mg}{k}" = "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}"
=> "v" = "\\frac {mg}{k}" + "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}"
So "v(t) =" "\\frac {mg}{k}" + "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}"
b)
For terminal velocity t→∞
So terminal velocity =
"\\lim_{t\u2192\u221e}v(t)"
= "\\lim_{t\u2192\u221e}" ["\\frac {mg}{k}" + "(v_0 - \\frac {mg}{k})""e^{-\\frac{k}{m}t}" ]
= "\\frac {mg}{k}" because "e^{-\\frac{k}{m}t}" →0 as t→∞
So terminal velocity is "\\frac {mg}{k}"
c)
"\\frac {ds}{dt}" = "\\frac {mg}{k}" + "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}"
"\\int" ds = "\\int" ["\\frac {mg}{k}" + "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}" ]dt
=> s = "\\frac {mg}{k}t" - "\\frac{m}{k}" "(v_0 - \\frac {mg}{k})" "e^{-\\frac{k}{m}t}" + D,
D is integration constant
From initial condition, s = 0, when t = 0
So D = "\\frac{m}{k}" "(v_0 - \\frac {mg}{k})"
s = "\\frac {mg}{k}t" + "\\frac {m}{k}" "(v_0 - \\frac {mg}{k})(1-e^{-\\frac{k}{m}t})"
s(t) =
"\\frac {mg}{k}t" + "\\frac {m}{k}" (v0- "\\frac {mg}{k}" )(1- "e^{-\\frac{k}{m}t}" )
Comments
Leave a comment